Tuning dCas9's ability to block transcription enables robust, noiseless knockdown of bacterial genes. Issue 3 (8th March 2018) - Vigouroux, Antoine; Oldewurtel, Enno; Cui, Lun; Bikard, David; van Teeffelen, Sven
Abstract: Over the past few years, tools that make use of the Cas9 nuclease have led to many breakthroughs, including in the control of gene expression. The catalytically dead variant of Cas9 known as dCas9 can be guided by small RNAs to block transcription of target genes, in a strategy also known as CRISPRi. Here, we reveal that the level of complementarity between the guide RNA and the target controls the rate at which RNA polymerase "kicks out" dCas9 from the target and completes transcription. We use this mechanism to precisely and robustly reduce gene expression by defined relative amounts. Alternatively, tuning repression by changing dCas9 concentration is noisy and promoter‐strength dependent. We demonstrate broad applicability of this method to the study of genetic regulation and cellular physiology. First, we characterize feedback strength of a model auto‐repressor. Second, we study the impact of amount variations of cell‐wall synthesizing enzymes on cell morphology. Finally, we multiplex the system to obtain any combination of fractional repression of two genes. Synopsis: When RNA polymerase encounters the dCas9 inactivated nuclease, it has a certain probability of going through depending on the guide RNA sequence. This property is exploited to robustly control the expression level of multiple genes from their native locus. For a high enough dCas9 concentration, the target locus can be saturated and repression strength only depends on the RNAP passage probability. Imperfect complementarity between the guide RNA and the target gene allows fine‐tuning passage probability and consequently gene expression levels. In saturating conditions, repression does not produce any additional noise on gene expression. This strategy is applied to measure the response of a genetic circuit, analyze how cell‐wall synthesis enzymes affect cell shape, and to tune the levels of multiple genes independently. Abstract : When RNA polymerase encounters the dCas9 inactivated nuclease, it has a certain probability of going through depending on the guide RNA sequence. This property is exploited to robustly control the expression level of multiple genes from their native locus.